Water and wastewater project development - Rendell, Frank (Thomas Telford, 1999)
Drawing on nearly 30 years' experience in the water industry the author provides instruction and guidance on the evaluation and decision-making processes involved in the conception and realisation of water and wastewater engineering projects.